2014
DOI: 10.1002/alr.21269
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes mellitus on chronic rhinosinusitis and sinus surgery outcome

Abstract: Objective Patients with diabetes mellitus (DM) are known to be liable to infection. However, the association between diabetes and chronic rhinosinusitis (CRS) has not been well studied. We sought to determine the effects of DM on CRS culture results and quality of life (QOL) after functional endoscopic sinus surgery (FESS). Methods We conducted a retrospective cohort study. Adult CRS patients undergoing FESS were recruited from 10/1/2007 to 12/31/2011. Patient demographics, comorbidities, medication use, Lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 42 publications
3
59
2
1
Order By: Relevance
“…This finding from our univariate analysis was reported in a recent publication of our team evaluating the effect of diabetes on CRS outcomes. 38 We found that diabetic patients were significantly more likely to have P. aeruginosa and Gramnegative rods as compared to nondiabetic patients. 38 However, because that previous article had a different focus, multivariate analysis was not performed to assess whether the association between diabetes and P. aeruginosa was significant after adjusting other clinical factors or was confounded by other clinical factors.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This finding from our univariate analysis was reported in a recent publication of our team evaluating the effect of diabetes on CRS outcomes. 38 We found that diabetic patients were significantly more likely to have P. aeruginosa and Gramnegative rods as compared to nondiabetic patients. 38 However, because that previous article had a different focus, multivariate analysis was not performed to assess whether the association between diabetes and P. aeruginosa was significant after adjusting other clinical factors or was confounded by other clinical factors.…”
Section: Discussionmentioning
confidence: 63%
“…38 We found that diabetic patients were significantly more likely to have P. aeruginosa and Gramnegative rods as compared to nondiabetic patients. 38 However, because that previous article had a different focus, multivariate analysis was not performed to assess whether the association between diabetes and P. aeruginosa was significant after adjusting other clinical factors or was confounded by other clinical factors. The association between P. aeruginosa and diabetes became marginally significant after adjusting for other clinical factors, but we cannot rule out the possibility that this is because of the small sample size of patients with P. aeruginosa.…”
Section: Discussionmentioning
confidence: 63%
“…4 This pathway may be particularly important for patients with CRS and/or diabetes mellitus because they exhibit elevated airway surface liquid glucose levels. 76,[83][84][85] …”
Section: Regulation Of Antimicrobial Compoundsmentioning
confidence: 99%
“…Recently, in a retrospective study of CRS patients, diabetics were found to be more likely to have intraoperative microbiology cultures that included gram-negative bacteria such as P. aeruginosa [212]. Previously, it has been speculated that keeping the ASL glucose concentrations low is important for keeping the airways sterile because it limits the nutrients available for bacteria to consume [207,205,206].…”
Section: Role Of Bitter and Sweet Taste Receptors In Upper Respiratormentioning
confidence: 99%